Abscesos pleurales producidos por Staphylococcus aureus y Streptococcus spp. beta-hemolítico como secuela de pleuroneumonía en un caballo. Reporte de un caso - Carmona R., Jorge Uriel; López, Catalina; Giraldo M., Carlos Eduardo (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary Pleural abscesses are a frequent complication in horses with pleuropneumonia. Their treatment is not easy, and requires time and it is expensive. A 13 years old creole argentine gelding presented a severe pleuropneumonia subsequently complicated with pleural abscess. The use of nonsteroidal antiinflammatory drugs (fenylbutazone), an aggressive antibiotherapy (ceftiofur, ampicillin, and gentamicin), echoguide drainage and lavage with yodopovidone to 0.05% of the abscesses permitted the successful recuperation of the patient of this case report.